Role of 8-isoprostane, Matrix Gla Protein (MGP) and Bone Morphogenetic Protein-2 (BMP-2) in Vascular Calcification in Chronic Kidney Disease - Wiwik Rositawati; Syakib Bakri; Gatot Susilo Lawrence; Andi Wijaya (The Indonesian Biomedical Journal, 2013)
BACKGROUND: Vascular calcification may be an important risk factor of cardiovascular disease in Chronic Kidney Disease (CKD). The pathobiology of vascular calcification in CKD is complex and involves some factors including inflammation, oxidative stress and balancing of calcification regulators. The aim of the study was to investigate the interaction between 8-isoprostane with calcification regulators such as matrix gla protein (MGP) and bone morphogenetic protein (BMP)-2 with vascular calciication in CKD.METHODS: A cross-sectional study was performed on 63 subjects undergoing haemodialysis maintenance for more than 3 months. Abdominal aortic calcification (AAC) was measured using a lateral abdominal X-ray for calcification in abdominal aorta, which is related to severity of calcific deposits at lumbar vertebral segment (L)1-L4. Serum levels of 8-isoprostane, MGP and BMP-2 were measured by enzyme-linked immunosorbent assay method.RESULTS: Results showed that 8-isoprostane levels were correlated with BMP-2 (r=0.266, p=0.018) and MGP levels (r=0.410, p≤0.001). MGP/BMP-2 levels ratio was correlated with AAC score (r=0.279, p=0.013). Subjects were then stratified into 3 groups based on AAC score: 0, 1-6 and ≥7. The highest mean of MGP levels was in AAC score 1-6 group, and the highest mean of 8-isoprostane levels was in AAC score ≥7. In the group of AAC score 0, 8-isoprostane levels were correlated with MGP levels (r=0.499, p=0.001) and MGP/BMP-2 levels ratio (r=0.291, p=0.034). In AAC score 1-6 group, 8-isoprostane levels were correlated with BMP-2 (r=0.661, p=0.005) and MGP levels (r=0.569, p=0.017). In AAC score ≥7 group, MGP levels were positively correlated with AAC score (r=0.608, p=0.041). With multivariate logistic regression analyses, we identified that increased MGP/BMP-2 levels ratio (OR=12.436; 95% CI=1.595-96.971) was an independent predictor in aortic calcification event.CONCLUSION: We concluded that regulators of calcification including calcification inhibitor and promoter related to oxidative stress, were associated with vascular calcification in CKD. MGP levels were increased in the early of calcification and MGP/BMP-2 levels ratio was a strong predictor for vascular calcification in CKD.KEYWORDS: vascular calcification, CKD, oxidative stress, 8-isoprostane, MGP, BMP-2